Obsessive Compulsive Disorder as a Presenting Symptom of COVID-19: A case-series from Iran - Mahsa Owji; Abdorreza Naser Moghadasi; Faezeh Gholamian; Seyed Yaser Mousavi (Babol University of Medical Sciences, 2022)
Background: Coronavirus disease 2019 (COVID-19) involves different organs and clinical presentations varying from respiratory symptoms to gastrointestinal symptoms and neurological symptoms. Another group of symptoms are psychiatric symptoms and according to a study, 53.8% of participants reported various degrees of these symptoms. Case Presentation: In this study, we presented six cases with sudden onset OCD or exacerbation of the previously controlled OCD concomitant with COVID-19 symptoms.Obsessive compulsive symptoms can be the presenting manifestation of COVID-19. Conclusion: The neuropsychiatric manifestations may be resulted from central nervous system (CNS) infiltration, and dysregulation of inflammatory factors autoimmune responses.